2021
DOI: 10.1002/jcp.30496
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine inhibits osteoclastogenesis by regulating calcium signaling and promotes osteogenesis

Abstract: Many bone diseases such as osteoporosis and periodontitis are caused by hyperactivation of osteoclasts. Calcium (Ca 2+ ) signals are crucial for osteoclast differentiation and function. Thus, the blockade of Ca 2+ signaling may be a strategy for regulating osteoclast activity and has clinical implications. Flunarizine (FN) is a Ca 2+ channel antagonist that has been used for reducing migraines. However, the role of FN in osteoclast differentiation and function remains unknown. Here, we investigated whether FN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…6 B). Among them, the pathway category “PI3K-Akt signaling pathway”, “Signaling pathways regulating pluripotency of stem cells”, “cGMP-PKG signaling pathway”, “Axon guidance”, and “Calcium signaling pathway” have previously been reported during osteogenic process [ 27 31 ]. The original data can be seen in Supplementary material 2 .…”
Section: Resultsmentioning
confidence: 99%
“…6 B). Among them, the pathway category “PI3K-Akt signaling pathway”, “Signaling pathways regulating pluripotency of stem cells”, “cGMP-PKG signaling pathway”, “Axon guidance”, and “Calcium signaling pathway” have previously been reported during osteogenic process [ 27 31 ]. The original data can be seen in Supplementary material 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the Wnt/β‐catenin signalling pathway can facilitate the production of bone marrow mesenchymal stem cells, mitigate ovariectomy‐induced bone loss, 51 and predominantly regulate osteoblast differentiation 52 . Calcium signals are crucial, and the blockade of calcium signalling has been proposed as a strategy for treating inflammatory bone diseases and postmenopausal osteoporosis 53 . It has been confirmed that many drugs can alleviate osteoporosis by promoting osteogenic differentiation and matrix mineralisation via the ERK signalling pathway 54 .…”
Section: Resultsmentioning
confidence: 99%
“…52 Calcium signals are crucial, and the blockade of calcium signalling has been proposed as a strategy for treating inflammatory bone diseases and postmenopausal osteoporosis. 53 It has been confirmed that many drugs can alleviate osteoporosis by promoting osteogenic differentiation and matrix mineralisation via the ERK signalling pathway. 54 So, it can be concluded that chemotaxonomic markers may alleviate osteoporosis via glycolysis, Wnt/β-catenin signalling, calcium signalling, ERK signalling, and so on.…”
Section: Analysis Of Chemotaxonomic Markers By Network Pharmacologymentioning
confidence: 99%
“…The level of individual mRNA was normalized to that of actin mRNA, which was used as an internal control gene. Most primers have been described previously (Hong et al, 2017; Jo et al, 2021; Kim, Lee, et al, 2021; Lee, Lee, et al, 2019; Lee, Son, et al, 2019; Son et al, 2020). The unique primer used in this study was that of Rora mRNA (5′‐GTGGAGACAAATCGTCAGGAAT‐3′ and 5′‐TGGTCCGATCAATCAAACAGTTC‐3′).…”
Section: Methodsmentioning
confidence: 99%